Incentivizing sleep? - Joan Costa-Font (IZA World of Labor, 2022)
Spending time sleeping not only improves individuals' well-being, but it can influence employment outcomes and productivity. Sleep can be disrupted by company schedules and deadlines, extended working times, and several individual and household decisions. Labor market regulation and corporate strategies should factor in the immediate effect of insufficient sleep on employee fatigue and cognitive performance, and the associated effects on employment disruption and productivity loss. Sleep can be influenced by "sleep friendly" employment regulations, technology nudges, monetary incentives, and subsidies for sleeping.
Keywords: I1; 330; sleep; employment; productivity; employment regulation; monetary incentives; technology nudges